2014
DOI: 10.1021/np5005246
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Resin Glycosides from Ipomoea aquatica and Their Effects on Intracellular Ca2+ Concentrations

Abstract: Eleven new resin glycosides, aquaterins I-XI (1-11), were isolated from the whole plants of Ipomoea aquatica. The structures of 1-11 were elucidated by a combination of spectroscopic and chemical methods. They were found to be partially acylated tetra- or pentasaccharides derived from simonic acid B and operculinic acids A and C. The site of the aglycone macrolactonization was placed at C-2 or C-3 of the second saccharide moiety, while the two acylating residues could be located at C-2 (or C-3) of the second r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…CE, a resin glycoside isolated from Ipomoea cairica , inhibited multiple tumor cells proliferation in our earlier study . Resin glycosides were reported to exert laxative properties, and had a potent anti‐tumor effect . AQP5, as an important regulator of body water metabolism, is critical to osmoregulation, may be involved in the laxative properties of resin glycosides.…”
Section: Discussionmentioning
confidence: 87%
“…CE, a resin glycoside isolated from Ipomoea cairica , inhibited multiple tumor cells proliferation in our earlier study . Resin glycosides were reported to exert laxative properties, and had a potent anti‐tumor effect . AQP5, as an important regulator of body water metabolism, is critical to osmoregulation, may be involved in the laxative properties of resin glycosides.…”
Section: Discussionmentioning
confidence: 87%
“…Sequential fractionation of active extracts with organic solvents, for example, petroleum ether, acetone, dichloromethane, ethyl acetate, butanol and methanol (Khlifi et al 2013;Tagne et al 2014) has also been reported. The cytotoxicity assay most widely used for estimating the anticancer potential of EFM is the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (Babykutty et al 2008;Fan et al 2014;Liu et al 2014;Park et al 2005), but other assays such as the sulphorhodamine B (SRB), neutral red, and lactate dehydrogenase (LDH) leakage assays have also been used (Aboul-Enein et al 2014;Prasad et al 2005;Rose et al 2005). The MTT assay gives an indication of whole cell cytotoxicity.…”
Section: Common Experimental Approachesmentioning
confidence: 99%
“…Flow cytometric analysis, apoptosis-specific assays (i.e., acridine orange/ethidium bromide staining; annexin/propidium iodide staining), mitochondrial membrane potential visualization assay, DNA fragmentation assay, gene expression analysis, reverse transcription-polymerase chain reaction (RT-PCR) assay, and Western blot analysis have been used to study the induction of apoptosis by extracts and compounds isolated from EFM (Aboul-Enein et al 2014;Babykutty et al 2008;Chen et al 2014;Dwarka 2012;Engel et al 2014;Hussin et al 2014;Zhang et al 2013b). Instrumental analyses such as reversed-phase high performance liquid chromatography (RP-HPLC), gas chromatography (GC), mass spectrometry (MS), infrared (IR) and nuclear magnetic resonance (1D and 2D NMR) (Boyd et al 2006;Fan et al 2014;Ooh et al 2014) were used to detect, characterize, and identify potential anticancer compounds from EFM.…”
Section: Common Experimental Approachesmentioning
confidence: 99%
See 2 more Smart Citations